Dietary supplementation of transient receptor potential vanilloid-1 channel agonists reduces serum total cholesterol level: a meta-analysis of controlled human trials. Issue 25 (1st September 2022) - Kelava, Leonardo; Nemeth, David; Hegyi, Peter; Keringer, Patrik; Kovacs, Dora K.; Balasko, Marta; Solymar, Margit; Pakai, Eszter; Rumbus, Zoltan; Garami, Andras
Abstract: Abnormal cholesterol level is a major risk factor in the development of atherosclerosis, which is a fundamental derangement in cardiovascular diseases. Any efforts should be undertaken to lower blood cholesterol levels. Among dietary interventions, capsaicinoid supplementation is also considered as a novel cholesterol-lowering approach, but human studies concluded contradictory results about its effectiveness. The present meta-analysis aimed at determining the effects of capsaicinoids on serum lipid profile in humans. We searched the PubMed, EMBASE, and CENTRAL databases from inception to February 2021. We included 10 controlled studies, which involved 398 participants. We found that dietary capsaicinoid supplementation alone or in combination with other substances significantly ( p  = 0.004 and 0.001, respectively) reduced serum total cholesterol level compared to controls with an overall standardized mean difference of −0.52 (95% confidence interval: −0.83, −0.21). Capsaicinoids also decreased low-density lipoprotein level significantly ( p  = 0.035), whereas no effect was observed on serum levels of high-density lipoprotein and triglycerides. Our findings provide novel quantitative evidence for the efficacy of dietary capsaicin supplementation in lowering serum total cholesterol and low-density lipoprotein levels in humans. To validate our conclusion, further randomized controlled trials in a diverse population of adult humans receiving dietary capsaicinoid supplementation are warranted.